Educational Thought According to Al-Ghazali and Ibnu Miskawaih - Firman Ashari (Elementaria: Journal of Educational Research, 2023)
In general, the thoughts of Al-Ghazali and Ibn Miskawaih reflect two different approaches to the synthesis between Greek philosophy and Islamic teachings. Al-Ghazali firmly rejected philosophy, while Ibn Miskawaih tried to integrate elements of philosophy into the framework of Islamic teachings more harmoniously. Both made important contributions to intellectual and ethical understanding in the context of medieval Islam. To provide a deeper understanding of Islamic intellectual and philosophical developments, as well as their contribution to global thought. The research method that will be used is library study, which involves searching for data and information from various sources available in the library. These sources include books, magazines, historical documents, and various other references. In this journal, data sources are divided into two categories, namely primary data (primary) and additional data (secondary). Because this research is a type of comparative study. As a result of this research, the thoughts of Al-Ghazali and Ibn Miskawaih made valuable contributions to the history of Islamic thought, especially in the fields of philosophy, ethics and education. Although both were Muslim scholars who lived during the same period, their approaches to various aspects of thought were different. Al-Ghazali and Ibn Miskawaih, as two key figures in the history of Islamic thought, showed different approaches in responding to issues of religion, philosophy, ethics and education. However, their legacy of thought continues to provide important contributions that continue to influence Islamic thought and also achieve a wider impact at the global level.